The Role of Product Quality, Innovation and Product Attractiveness on Consumer Satisfaction of PORTO X Products - Wardhana, M Adhitya; Hayati, Nur (Universitas Muhammadiyah Surakarta, 2025)
In the current era, competition in the manufacturing industry is very tight and fierce, especially in this case the footwear manufacturing or production industry. Many footwear brands in Indonesia are competing to produce the best footwear products, for example PORTO X. PORTO X is a footwear sandal brand that is present and tries to produce and maintain Product Quality, Innovation, to make Consumer Attraction to buy and feel Satisfaction after buying it. This research was conducted to examine the extent to which PORTO X maintains its Quality and Innovation by using a quality approach method by obtaining data based on documentation from various sources. In the end, PORTO X is very committed to being able to maintain the Quality of its Products and Innovation well, this is what makes many of their products sell well in the market, because they have Attraction and have bought Satisfaction for their users.